2009
DOI: 10.1017/s0007114509993242
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on seaweed consumption and the risk of breast cancer

Abstract: Gim (Porphyra sp.) and miyeok (Undaria pinnatifida) are the seaweeds most consumed by Koreans. We investigated the association between the intake of gim and miyeok and the risk of breast cancer in a case -control study. Cases were 362 women aged 30 -65 years old, who were histologically confirmed to have breast cancer. Controls visiting the same hospital were matched to cases according to their age (SD 2 years) and menopausal status. Food intake was estimated by the quantitative FFQ with 121 items, including g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 47 publications
0
58
2
Order By: Relevance
“…There was no apparent visible difference in the appearance of the seaweed bread compared to the placebo bread. The daily dosage of P. palmata selected for this study was based on the reported seaweed intake in Asian populations (5.3 g/day in Japan to 8.5 g/d in Korea) where beneficial effects have been reported [1,2]. The composition of the bread consumed by the participants each day was as follows: 165 g fibremalt, 60 ml water, 5 g P. palmata, 1 g salt, 1 g dough improver, 7 g fresh yeast and 13 g honey.…”
Section: Seaweed Collection and Preparation For Breadmentioning
confidence: 99%
“…There was no apparent visible difference in the appearance of the seaweed bread compared to the placebo bread. The daily dosage of P. palmata selected for this study was based on the reported seaweed intake in Asian populations (5.3 g/day in Japan to 8.5 g/d in Korea) where beneficial effects have been reported [1,2]. The composition of the bread consumed by the participants each day was as follows: 165 g fibremalt, 60 ml water, 5 g P. palmata, 1 g salt, 1 g dough improver, 7 g fresh yeast and 13 g honey.…”
Section: Seaweed Collection and Preparation For Breadmentioning
confidence: 99%
“…Nevertheless, epidemiological information concerning the effects of seaweed consumption has been scarce. Inverse associations have been reported between seaweed consumption and stomach cancer [2], colorectal cancer [3], allergic rhinitis [4], mortality from all causes, pancreatic cancer, lung cancer, kidney cancer, and cerebrovascular disease [5], breast cancer [6], and elevated blood pressure [7], while positive associations have been shown between seaweed consumption and prostate cancer [8], upper aerodigestive tract cancer [9], mortality from colon cancer [5], metabolic syndrome [10], and thyroid cancer [11]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, ␤-carotene and lutein were identified as antimutagenic substances in edible red algae, which indicated their potential anticancer activity (3). Furthermore, studies on mice/rats and humans demonstrated that dietary supplementation with various extracts of a variety of seaweeds correlated with a decreased risk of breast cancer (4,5). Polysaccharides, proteins, peptides, and amino acids from a number of seaweeds showed beneficial activity against diabetes, cancer, AIDS, and vascular diseases (2).…”
mentioning
confidence: 99%